PRIMARY HYPOADRENOCORTICISM IN A DOG - Anjos, Denner Santos dos; Babo-Terra, Veronica Jorge; Palumbo, Mariana Isa Poci (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2016)
This report describes the clinical and laboratorial findings as well as the therapeutic protocol performed in a three-year-old mongrel female intact dog, referred to the Veterinary Hospital of FAMEZ/UFMS. The animal had a previous history of recurrent gastrointestinal signs (such as lethargy, vomiting, loss of appetite, melena and abdominal pain), acute crisis episodes, bradycardia, hypotension, hypothermia and increase of capillary refill time, recognized as addisonian crisis due to primary hypoadrenocorticism. Laboratorial findings included anemia, eosinophilia, neutrophilia, lymphocytosis, sodium-potassium ratio of 14,02 mEq/L and prerenal azotemia. Based on that, it was confirmed the diagnosis of primary hypoadrenocorcitism. Thus, it was recommended supplementation therapy with mineralocorticoid (aldosterone) and glucocorticoid (cortisol) corresponding respectively, fludrocortisone acetate of 0.2 mg per kg of BW, by mouth, once daily and prednisone 0.2 mg per kg of BW, by mouth, twice daily until further recommendations. The prognostic was excellent, since the animal significantly improved body condition, andclinical signs disappeared after therapy which lead the sodium-potassium ratio to 35.11 mEq/L. Thus, the clinician must always suspect of primary hypoadrenocorticism in dogs with intermittent nonspecific signs that get better with support therapy. Presumably, hypoarenocorticism must be under diagnosed in veterinary medicine, reinforcing the need to require specific exams in patients that show this wax and wane feature of clinical signs.